Surfactant-enhanced remediation of soils contaminated with petroleum hydrocarbons. (1st January 2013) - Singh, S.K.; John, Siby
An experimental programme was undertaken to reclaim the soils contaminated with petroleum hydrocarbons. Two types of locally available soils, clay with low compressibility and poorly graded sand, were chosen for the study. Both the soils were contaminated with varying percentages of used engine oil and gasoline. Anionic surfactant Sodium Dodecyl Sulphate (SDS) was used to reclaim the contaminated soil. Geotechnical properties of virgin (uncontaminated) and contaminated and reclaimed soil were determined. It was observed that original geotechnical properties of soil could be restored on decontamination with SDS at optimum dose. The Fourier Transform Infra Red (FTIR) spectra on contaminated and decontaminated samples confirmed the physical removal of contaminants from soil matrix on washing.